Iranian healthcare workers' perspective on hand hygiene: A qualitative study. Issue 1 (January 2015) - McLaws, Mary-Louise; Farahangiz, Saman; Palenik, Charles J.; Askarian, Mehrdad
Summary Background Hand hygiene (HH) has been identified as one of the simplest, but most important, methods to prevent cross-infection in healthcare facilities. In spite of this fact, the HH compliance rate remains low among healthcare workers (HCWs). Several factors may affect HH behavior. In this study, we aimed to assess various aspects of HH from the perspective of HCWs. Method This qualitative study was conducted in two hospital settings in Shiraz, Iran. Eight focus group discussions (FGDs) and six in-depth interview sessions were held with ICU and surgical ward nurses, attending physicians, medical and nursing students and supporting staff. Each FGD and interview was transcribed verbatim, open codes were extracted, and thematic analysis was conducted. Results Three themes emerged from the thematic analysis including: "the relationship between personal factors and HH compliance, " "the relationship between environmental factors and HH compliance" and "the impact of the health system on HH adherence, including the role of adequate health systems, administrative obligations and the effect of surveillance systems." Conclusion Several factors played a significant role in improving HCWs HH compliance, such as the regular adherence to health system tenets. HH compliance may be improved through application of realistic policies and better supervision. In addition, appropriate education may positively affect HH behavior and attitudes.